Overview of decentralization worldwide a stepping stone to improved governance and human development - Work, Robertson (Philippine Journal of Public Administration, 2002)
While there may be numerous initiatives for implementing decentralization policies, not to mention the varying types and degrees of decentralization worldwide, it is inherently difficult to compare a single notion of decentralization. The lines between the forms of decentralization and existing government systems become quite blurred in practice. In order to accurately summarize the degree of decentralization in a country, one must simultaneously consider the political, fiscal and administrative issues at all tiers of government as well as local council elections, participatory budgeting practices, local government's borrowing papers and tax collection capacity, the prevalence and role of NGOs and advocacy groups, community organizing and freedom of voice. Definitely, as evident from the varied experiences in decentralization around the world, there is no "one-size fits all" design of decentralization policies. Instead decentralization has to be sensitive to the existing cultural, political and institutional arrangements within a particular country. Although there are many successful examples of decentralization and sustainable human development, there is much room for needed improvement. Further analysis is necessary in order to better understand which forms and under what circumstances decentralization can have a productive role in supporting sustainable human development and how governments and stakeholders should approach these processes.